2022
DOI: 10.1111/bcp.15222
|View full text |Cite
|
Sign up to set email alerts
|

The effects of saffron (Crocus sativus L.) in conjunction with concurrent training on body composition, glycaemic status, and inflammatory markers in obese men with type 2 diabetes mellitus: A randomized double‐blind clinical trial

Abstract: Aims Chronic inflammation is one of the major challenges in the management of obesity and type 2 diabetes mellitus (T2DM). Our primary aim was to assess the anti‐inflammatory effects of Saffron (Crocus sativus L.) supplementation and concurrent training in obese men with T2DM. Methods Sixty obese men with T2DM (age = 39 ± 5 years; body mass = 93.9 ± 6 kg) were randomly assigned to four groups; concurrent training + placebo (CT; n = 15), saffron supplementation (S; n = 15), concurrent training + saffron supplem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 71 publications
0
7
0
Order By: Relevance
“…The studies included a total of 2398 participants with an age range of between 30 and 70 years. Thirty studies recruited subjects with T2DM [ 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 ], one study included prediabetic and newly diagnosed diabetic subjects [ 97 ], and another study involved participants diagnosed with T2DM alongside obese individuals [ 98 ]. Eight studies reported a single-arm intervention in T2DM subjects, one supplemented with rosemary [ 70 ], three analyzed the effect of black cumin [ 74 , 76 , 98 ] on the glycemic profile, three supplemented with curcumin [ 77 , 81 , 82 ], and one examined the effect of ginger on the glycemic profile [ 89 ].…”
Section: Resultsmentioning
confidence: 99%
“…The studies included a total of 2398 participants with an age range of between 30 and 70 years. Thirty studies recruited subjects with T2DM [ 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 ], one study included prediabetic and newly diagnosed diabetic subjects [ 97 ], and another study involved participants diagnosed with T2DM alongside obese individuals [ 98 ]. Eight studies reported a single-arm intervention in T2DM subjects, one supplemented with rosemary [ 70 ], three analyzed the effect of black cumin [ 74 , 76 , 98 ] on the glycemic profile, three supplemented with curcumin [ 77 , 81 , 82 ], and one examined the effect of ginger on the glycemic profile [ 89 ].…”
Section: Resultsmentioning
confidence: 99%
“…With a limitation of extremely low yield and labor extensive handling, saffron production usually comes with high costs. However, it continuously attracts numerous studies for various health-related diseases in human subjects, such as inflammatory status of elderly hypertensive men ( Mojtahedi et al, 2022 ), obese men with type 2 diabetes mellitus ( Hooshmand Moghadam et al, 2022 ), chemotherapy-induced peripheral neuropathy ( Bozorgi et al, 2021 ), and it has been shown to increase happiness as it reduces depression ( Moghadam et al, 2021 ). In Iran, the dried, red stigmas of the C. sativus are thought to be a stimulant with anti-spasmodic action and are also a favorite coloring spice in food ( Parsa, 1959b ).…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that saffron extract or crocin has the potential to improve glycemic profile in DM. A previous RCT reported that saffron supplementation significantly lowered FPG, HbA1c, insulin levels and HOMA-IR in obese men with T2DM (46). Another recent RCT revealed that 400 mg daily saffron supplementation in combination with 8 weeks aerobic training, could improve blood glucose, insulin levels and HOMA-IR in middle-aged overweight female patients with T2DM (47).…”
Section: Discussionmentioning
confidence: 99%